Preparation method of recombinant collagen nano-composite hydrogel for repairing wound infected by multiple drug-resistant bacteria
By introducing MXene@CuTCPP composite nanoparticles and polyvinyl alcohol into recombinant collagen nanocomposite hydrogels, combined with photothermal treatment, the antibacterial and healing problems of multidrug-resistant bacteria infected wounds are solved, and efficient wound management and treatment are achieved Effect.
Patent Information
- Application Number
- CN202411387720.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-07
- Publication Date
- 2025-01-14
AI Technical Summary
In the prior art, when dealing with multidrug-resistant bacteria infected wounds, the abuse of antibiotics leads to increased drug resistance. The limitations and side effects of traditional hydrogels are difficult to effectively solve, and it is difficult to achieve efficient antibacterial and wound healing.
Modified recombinant collagen nanocomposite hydrogel containing MXene@CuTCPP composite nanoparticles is adopted to form a heterojunction structure through photothermal therapy and photodynamic therapy, combined with the dynamic cross-linking characteristics of polyvinyl alcohol, and realize the formation of heterojunction structures against multidrug-resistant bacteria. Efficient sterilization and wound repair of infection.
This method can fit the wound tightly, achieve efficient antibacterial and promote wound healing, has excellent biocompatibility and self-healing performance, and significantly improves the therapeutic effect of multidrug-resistant bacteria infection.
Smart Images

Figure CN119303152A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomaterials, and in particular relates to a method for preparing a recombinant collagen nanocomposite hydrogel for repairing wounds infected by multi-drug resistant bacteria. Background Art
[0002] The skin is a protective barrier between internal organs and other parts of the outside world, but the skin is susceptible to bacterial infection, which has become a common problem that hinders normal wound healing and skin formation, which will lead to long-term chronic inflammation and infection. For bacterially infected wounds, the common clinical method is to treat them with antibiotics, but the abuse of antibiotics can cause bacteria to develop drug resistance and then become multidrug-resistant (MDR) bacteria, endangering the efficacy of antibiotic treatment. If more uncontrollable drug-resistant bacteria remain in the body, antibiotics will not work well in the event of sudden severe illness, and will also produce side effects such as gastrointestinal irritation, vomiting, and intestinal disorders. It is estimated that by 2050, MDR bacterial infections will cause more than 10 million deaths. How to improve the antibacterial effect of MDR bacterial infected wounds is a problem to be explored. In order to effectively eradicate MDR bacteria and reduce the use of antibiotics, in the face of the rampant and difficult-to-remove characteristics of MDR bacteria, the antibacterial method of combining nano-antibacterial agents has been proposed in recent years. The antibacterial properties of hydrogels based on nanomaterials have been widely studied. Because it involves multiple antibacterial mechanisms, it is expected to become an effective alternative to antibiotics.
[0003] In recent years, in the field of wound repair, the research hotspot of refractory wound treatment is to use hydrogel as a carrier and further incorporate specific antibacterial nanoparticles to construct nanocomposite hydrogels, which are applied to MDR bacterial infection wounds. By utilizing the good biocompatibility of hydrogel dressings, the 3D microenvironment that mimics the extracellular matrix, and the viscoelasticity similar to natural skin tissue, a scaffold that supports cell growth is provided to form an anti-infection barrier, thereby promoting the natural coagulation of blood, blocking nerve endings to relieve pain, and absorbing wound exudate. Compared with traditional hydrogel dressings, nanocomposite hydrogels evenly disperse nanoparticles or nanostructured materials in the polymer network, and form a hydrogel network through physical or chemical crosslinking. It has excellent mechanical, optical, self-healing, and swelling / contraction properties, while overcoming the limitations of traditional chemically crosslinked hydrogels. It is a new type of intelligent material with great application potential. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a recombinant collagen nanocomposite hydrogel for repairing wounds infected by multidrug-resistant bacteria in view of the deficiencies of the above-mentioned prior art. The method uses a modified recombinant collagen system containing MXene@CuTCPP composite nanoparticles and a polyvinyl alcohol solution as the main raw materials, and obtains a recombinant collagen nanocomposite hydrogel for repairing wounds infected by multidrug-resistant bacteria by stirring and mixing. The recombinant collagen nanocomposite hydrogel can fit the wounds infected by multidrug-resistant bacteria tightly, can be treated by photothermal therapy and photodynamic therapy, has both antibacterial properties and self-healing properties, and can comprehensively and efficiently manage and treat wounds at the infected site.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a recombinant collagen nanocomposite hydrogel for repairing wounds infected with multi-drug resistant bacteria, characterized in that it comprises the following steps:
[0006] Step 1: Prepare MXene@CuTCPP composite nanoparticles using MXene nanosheets and copper porphyrin nanosheets;
[0007] Step 2: using EDC and NHS to modify the recombinant collagen to obtain modified recombinant collagen;
[0008] Step 3, sterilizing the MXene@CuTCPP composite nanoparticles prepared in step 1 by Co60 irradiation;
[0009] Step 4, dissolving the modified recombinant collagen described in step 2 in a phosphate buffer solution to obtain a modified recombinant collagen solution with a mass concentration of 10% to 15%;
[0010] Step 5: Mix the sterilized MXene@CuTCPP composite nanoparticles in step 3 with the modified recombinant collagen solution in step 4, and stir for 1 min to 2 min to obtain system A;
[0011] Step 6: Add the system A described in step 5 into the polyvinyl alcohol solution and mix them evenly to obtain a recombinant collagen nanocomposite hydrogel for repairing wounds infected with multidrug-resistant bacteria.
[0012] The above-mentioned method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multi-drug resistant bacteria is characterized in that the method for preparing the MXene@CuTCPP composite nanoparticles in step 1 specifically comprises:
[0013] Step 101, etching titanium aluminum carbide with hydrofluoric acid for 12 hours to 96 hours, centrifuging, and drying to obtain MXene multilayer nanosheets;
[0014] Step 102, exfoliating the MXene multilayer nanosheets described in step 101 with a tetramethylammonium hydroxide solution for 12 h to 48 h, centrifuging, and drying to obtain a few-layer MXene nanosheet;
[0015] Step 103, uniformly dispersing tetrakis(4-carboxyphenyl)porphine in a mixed solution of N,N-dimethylformamide and ethanol by ultrasonication to obtain a tetrakis(4-carboxyphenyl)porphine suspension, adding cupric chloride dihydrate and polyvinyl pyrrolidone to the suspension, heating in a water bath at 70° C. to 90° C., vigorously stirring for 5 h to 9 h, centrifuging and freeze-drying to obtain copper porphyrin nanosheets;
[0016] Step 104: Ultrasonically uniformly disperse the MXene nanosheets described in step 102 and the copper porphyrin nanosheets described in step 103 in a mixed solution of N,N-dimethylformamide and ethanol to obtain a suspension containing copper porphyrin and MXene, heat in a water bath at 70° C. to 90° C., vigorously stir for 5 h to 9 h, centrifuge, and freeze-dry to obtain MXene@CuTCPP nanosheets.
[0017] The above-mentioned method for preparing recombinant collagen nanocomposite hydrogel for repairing wounds infected with multidrug-resistant bacteria is characterized in that the mass of the hydrofluoric acid described in step 101 is 5 to 10 times the mass of titanium aluminum carbide, and the mass percentage of the hydrofluoric acid is 30% to 45%; the mass of the tetramethylammonium hydroxide solution described in step 102 is 5 to 10 times the mass of titanium aluminum carbide, and the mass percentage of tetramethylammonium hydroxide in the tetramethylammonium hydroxide solution is 25% to 50%.
[0018] The above-mentioned method for preparing recombinant collagen nanocomposite hydrogel for repairing wounds infected with multidrug-resistant bacteria is characterized in that the volume ratio of N,N-dimethylformamide to ethanol in the mixed solution of N,N-dimethylformamide and ethanol in step 103 is (3-4):1; the ratio of the mass of the tetrakis(4-carboxyphenyl)porphine to the volume of the mixed solution of N,N-dimethylformamide and ethanol is (4-5):1, wherein the unit of mass is mg and the unit of volume is mL; the mass of the tetrakis(4-carboxyphenyl)porphine is the mass of cupric chloride dihydrate. The mass of polyvinyl pyrrolidone is 150% to 200% of the mass of cupric chloride dihydrate, and the mass of polyvinyl pyrrolidone is 100% to 130% of the mass of cupric chloride dihydrate; in the mixed solution of N,N-dimethylformamide and ethanol in step 104, the volume ratio of N,N-dimethylformamide to ethanol is (3 to 4):1, the mass of the MXene nanosheets is 80% to 150% of the mass of the copper porphyrin nanosheets, and the ratio of the mass of the MXene nanosheets to the volume of the mixed solution of N,N-dimethylformamide and ethanol is (4 to 5):1, wherein the unit of mass is mg and the unit of volume is mL.
[0019] The above-mentioned method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multi-drug resistant bacteria is characterized in that the modification method in step 2 specifically includes:
[0020] Step 201, dissolving recombinant collagen, EDC and NHS in a phosphate buffer solution to obtain a mixed solution, stirring and activating the mixed solution at a temperature of 20° C. to 37° C. for 1 h to 3 h to obtain an activated recombinant collagen solution;
[0021] Step 202, mixing the recombinant collagen solution activated in step 201 and the buffer solution containing 3-aminophenylboronic acid, stirring and reacting at a temperature of 20°C to 37°C for 12h to 16h, dialyzing the system after the stirring reaction, and freeze-drying to obtain modified recombinant collagen.
[0022] The method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multidrug-resistant bacteria is characterized in that the pH of the mixed solution in step 201 is 3-4; the mass of the recombinant collagen is 4%-5% of the mass of the phosphate buffer solution.
[0023] The above-mentioned method for preparing recombinant collagen nanocomposite hydrogel for repairing wounds infected with multidrug-resistant bacteria is characterized in that the recombinant collagen described in step 201 is recombinant collagen CF-1552, and the amount of recombinant collagen substance is 1.5 times to 2 times the amount of 3-aminophenylboronic acid substance in step 202; the buffer solution containing 3-aminophenylboronic acid described in step 202 is a buffer solution prepared by dissolving 3-aminophenylboronic acid in phosphate buffer, and the mass percentage of 3-aminophenylboronic acid in the buffer solution is 4% to 5%; the amount ratio of 3-aminophenylboronic acid, EDC and NHS is (1 to 1.5):1:1.
[0024] The above-mentioned method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multidrug-resistant bacteria is characterized in that the mass percentage of the MXene@CuTCPP composite nanoparticles in the system A described in step five is 0.2% to 0.5%.
[0025] The above-mentioned method for preparing recombinant collagen nanocomposite hydrogel for repairing wounds infected with multidrug-resistant bacteria is characterized in that the polyvinyl alcohol solution in step six is a polyvinyl alcohol aqueous solution with a mass concentration of 10% to 15%, and the molecular weight of the polyvinyl alcohol is 89,000 to 98,000.
[0026] 10. The method for preparing recombinant collagen nanocomposite hydrogel for repairing wounds infected with multidrug-resistant bacteria according to claim 1, characterized in that the mass ratio of the polyvinyl alcohol solution and system A in step six is (1-2):(1-2).
[0027] The present invention forms MXene@CuTCPP nanoparticles by π-π conjugation of copper porphyrin (CuTCPP) on titanium carbide (MXene) nanosheets, performs amidation reaction on 3-aminophenylboronic acid and recombinant collagen to obtain modified recombinant collagen, and mixes MXene@CuTCPP into the modified recombinant collagen system and polyvinyl alcohol solution to prepare recombinant collagen nanocomposite hydrogel; the self-healing performance given by the dynamic cross-linking characteristics of phenylboronic acid ester bonds in the prepared composite hydrogel can be highly adapted to irregular wounds; the nanoparticles with heterojunction structure can be combined with photothermal therapy and photodynamic therapy to efficiently sterilize wounds; the raw materials used in the material are all biosafe and can be safely used for wound treatment. Therefore, combined with the above characteristics, the hydrogel has both antibacterial properties and wound healing promotion properties, and can be comprehensively and efficiently treated for wounds infected with multi-drug resistant bacteria.
[0028] Compared with the prior art, the present invention has the following advantages:
[0029] 1. The present invention modifies the hydrogel by using recombinant collagen protein and polyvinyl alcohol as the main skeleton of the hydrogel, and incorporates MXene@CuTCPP composite nanoparticles to obtain a recombinant collagen nanocomposite hydrogel for repairing wounds infected with multidrug-resistant bacteria. The hydrogel can fit tightly to wounds infected with multidrug-resistant bacteria, and can be combined with photothermal therapy and photodynamic therapy to achieve efficient antibacterial properties under the joint action of the two treatment strategies. It has both antibacterial properties and self-healing properties, and can comprehensively and efficiently treat wounds at the infected site.
[0030] 2. The present invention preferably obtains a MXene@CuTCPP composite nanostructure by loading copper-containing porphyrin on MXene nanosheets. The heterojunction structure nanosheets obtained by combining the two are incorporated into the hydrogel system, which can effectively improve the antibacterial properties of the hydrogel.
[0031] 3. The present invention loads nanoparticles MXene@CuTCPP into a hydrogel dynamically cross-linked with recombinant collagen and polyvinyl alcohol, which can realize its intelligent release in different wound environments. MXene@CuTCPP and recombinant collagen respectively give the hydrogel the biological properties of rapid antibacterial and promotion of wound repair.
[0032] 4. The present invention uses recombinant collagen to provide beneficial ingredients for wounds and significantly promote wound healing. Recombinant collagen CF-1552 is preferred. Compared with collagen from other animal sources, CF-1552 has excellent biocompatibility, good water solubility, is virus-free, and has low immunogenicity.
[0033] 5. The preparation method of the present invention is simple, has good reproducibility, and has good application prospects.
[0034] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Schematic diagram of the preparation process of the few-layer MXene nanosheets and MXene@CuTcpp composite nanoparticles of the present invention.
[0036] Figure 2 It is the SEM image and mapping element distribution diagram of the MXene@CuTCPP composite nanoparticles of the present invention.
[0037] Figure 3 This is the XRD diagram of the MXene@CuTCPP composite nanoparticles of the present invention.
[0038] Figure 4 This is the FTIR spectrum of the modified recombinant collagen of Example 1 of the present invention, CF-1552 is the recombinant collagen, and APBA-CF-1552 is the modified recombinant collagen.
[0039] Figure 5 This is a morphology diagram of the recombinant collagen nanocomposite hydrogel used for repairing wounds infected with multi-drug resistant bacteria in Example 1 of the present invention.
[0040] Figure 6 This is a SEM image of the recombinant collagen nanocomposite hydrogel used for repairing wounds infected with multi-drug resistant bacteria in Example 1 of the present invention.
[0041] Figure 7 This is the cytotoxicity test result of the recombinant collagen nanocomposite hydrogel used for repairing wounds infected with multi-drug resistant bacteria in Example 1 of the present invention.
[0042] Figure 8 These are the test results of the cell migration promoting ability of the recombinant collagen nanocomposite hydrogel used for repairing wounds infected with multidrug-resistant bacteria in Example 1 of the present invention.
[0043] Fig. 9 Survival rate of MRSA at different MXene@CuTCPP concentrations.
[0044] Fig.10 Survival rate of E. coli at different MXene@CuTCPP concentrations.
[0045] Fig.11 Survival rate of S. aureus at different MXene@CuTCPP concentrations.
[0046] Fig.12 Survival rate of S. aureus under different hydrogel treatments.
[0047] Fig.13 The survival rate of E. coli under different hydrogel treatments.
[0048] Fig.14 is the survival rate of MRSA under different hydrogel treatments. DETAILED DESCRIPTION
[0049] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail in combination with the examples below. The recombinant collagen described in the following examples is CF-1552, which is derived from the Institute of Biomedicine, School of Chemical Engineering, Northwest University. The recombinant collagen CF-1552 is a human collagen mRNA reverse transcribed to generate cDNA, and then expressed in Escherichia coli BL21. Its structure and acquisition method can refer to the patent application document with patent number ZL01106757.8 and patent name "A human-like collagen and its production method", or the document Recombinant collagen for the repair of skin wounds and photo-aging damage, Regenerative Biomaterials, 2024, 11, rbae108. In the description of the present invention, unless otherwise specified, the reagents used are commercially available.
[0050] The method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multi-drug resistant bacteria of the present invention comprises the following steps:
[0051] Step 1: Prepare MXene@CuTCPP composite nanoparticles using MXene nanosheets and copper porphyrin nanosheets; the schematic diagram of the preparation process of few-layer MXene nanosheets and MXene@CuTcpp composite nanoparticles is shown in Figure 1 , the specific preparation method comprises:
[0052] Step 101, etching titanium aluminum carbide with hydrofluoric acid for 12 hours to 96 hours, centrifuging, and drying to obtain MXene multilayer nanosheets; the mass of the hydrofluoric acid is 5 to 10 times the mass of the titanium aluminum carbide, and the mass percentage of the hydrofluoric acid is 30% to 45%;
[0053] Step 102, exfoliating the MXene multilayer nanosheets in step 101 with a tetramethylammonium hydroxide solution for 12 hours to 48 hours, centrifuging, and drying to obtain a few-layer MXene nanosheet; the mass of the tetramethylammonium hydroxide solution is 5 to 10 times the mass of titanium aluminum carbide, and the mass percentage of tetramethylammonium hydroxide in the tetramethylammonium hydroxide solution is 25% to 50%;
[0054] Step 103, uniformly dispersing tetrakis(4-carboxyphenyl)porphine in a mixed solution of N,N-dimethylformamide and ethanol by ultrasonication to obtain a tetrakis(4-carboxyphenyl)porphine suspension, adding cupric chloride dihydrate and polyvinyl pyrrolidone to the suspension, heating in a water bath at 70° C. to 90° C., vigorously stirring for 5 h to 9 h, centrifuging and freeze-drying to obtain copper porphyrin nanosheets; N,N-dimethylformamide in the mixed solution of ethanol The volume ratio of tetrakis(4-carboxyphenyl)porphine to ethanol is (3-4):1; the ratio of the mass of the tetrakis(4-carboxyphenyl)porphine to the volume of the mixed solution of N,N-dimethylformamide and ethanol is (4-5):1, wherein the unit of mass is mg and the unit of volume is mL; the mass of the tetrakis(4-carboxyphenyl)porphine is 150%-200% of the mass of cupric chloride dihydrate, and the mass of polyvinylpyrrolidone is 100%-130% of the mass of cupric chloride dihydrate;
[0055] Step 104, ultrasonically uniformly dispersing the MXene nanosheets described in step 102 and the copper porphyrin nanosheets described in step 103 in a mixed solution of N,N-dimethylformamide and ethanol to obtain a suspension containing copper porphyrin and MXene, heating in a water bath at 70°C to 90°C, vigorously stirring for 5h to 9h, centrifuging, and freeze-drying to obtain MXene@CuTCPP nanosheets; the volume ratio of N,N-dimethylformamide to ethanol in the mixed solution of N,N-dimethylformamide and ethanol is (3-4):1, the mass of the MXene nanosheets is 80% to 150% of the mass of the copper porphyrin nanosheets, and the ratio of the mass of the MXene nanosheets to the volume of the mixed solution of N,N-dimethylformamide and ethanol is (4-5):1, wherein the unit of mass is mg and the unit of volume is mL;
[0056] Step 2: using EDC and NHS to modify the recombinant collagen to obtain modified recombinant collagen; the specific modification method includes:
[0057] Step 201, dissolving recombinant collagen, EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride) and NHS (N-hydroxysuccinimide) in a phosphate buffer solution to obtain a mixed solution, stirring and activating the mixed solution at a temperature of 20° C. to 37° C. for 1 h to 3 h to obtain an activated recombinant collagen solution; the pH of the mixed solution is 3 to 4; the mass of the recombinant collagen is 4% to 5% of the mass of the phosphate buffer solution;
[0058] Step 202, mixing the recombinant collagen solution activated in step 201 and the buffer solution containing 3-aminophenylboronic acid, stirring and reacting at a temperature of 20° C. to 37° C. for 12 h to 16 h, dialyzing the system after the stirring reaction, and freeze-drying to obtain modified recombinant collagen; the amount of the recombinant collagen substance is 1.5 to 2 times the amount of the 3-aminophenylboronic acid substance; the buffer solution containing 3-aminophenylboronic acid is a buffer solution prepared by dissolving 3-aminophenylboronic acid in phosphate buffer, and the mass percentage of 3-aminophenylboronic acid in the buffer solution is 4% to 5%; the amount ratio of 3-aminophenylboronic acid, EDC and NHS is (1 to 1.5):1:1;
[0059] Step 3, sterilizing the MXene@CuTCPP composite nanoparticles prepared in step 1 by Co60 irradiation;
[0060] Step 4, dissolving the modified recombinant collagen described in step 2 in a phosphate buffer solution to obtain a modified recombinant collagen solution with a mass concentration of 10% to 15%;
[0061] Step 5: Mix the sterilized MXene@CuTCPP composite nanoparticles in step 3 with the modified recombinant collagen solution in step 4, and stir for 1 min to 2 min to obtain system A; the mass percentage of MXene@CuTCPP composite nanoparticles in system A is 0.2% to 0.5%;
[0062] Step six, adding the system A described in step five to the polyvinyl alcohol solution, mixing evenly, to obtain a recombinant collagen nanocomposite hydrogel for repairing wounds infected with multidrug-resistant bacteria; the polyvinyl alcohol solution is a polyvinyl alcohol aqueous solution with a mass concentration of 10% to 15%, and the molecular weight of polyvinyl alcohol is 89,000 to 98,000; the mass ratio of the polyvinyl alcohol solution to the system A is (1 to 2): (1 to 2).
[0063] Example 1
[0064] The method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multi-drug resistant bacteria of this embodiment comprises the following steps:
[0065] Step 1: Prepare MXene@CuTCPP composite nanoparticles using MXene nanosheets and copper porphyrin nanosheets; the specific preparation method includes:
[0066] Step 101, etching titanium aluminum carbide with hydrofluoric acid for 24 hours, centrifuging, and drying to obtain MXene multilayer nanosheets; the mass of the hydrofluoric acid is 5 times the mass of the titanium aluminum carbide, and the mass percentage of the hydrofluoric acid is 40%;
[0067] Step 102, exfoliating the MXene multilayer nanosheets in step 101 with a tetramethylammonium hydroxide solution for 12 hours, centrifuging, and drying to obtain a few-layer MXene nanosheet; the mass of the tetramethylammonium hydroxide solution is 5 times the mass of titanium aluminum carbide, and the mass percentage of tetramethylammonium hydroxide in the tetramethylammonium hydroxide solution is 25%;
[0068] Step 103, ultrasonically uniformly dispersing tetrakis(4-carboxyphenyl)porphine in a mixed solution of N,N-dimethylformamide and ethanol to obtain a tetrakis(4-carboxyphenyl)porphine suspension, adding cupric chloride dihydrate and polyvinyl pyrrolidone to the suspension, heating in a water bath at 80° C., vigorously stirring for 5 h, centrifuging and collecting at a speed of 8000 rpm, and then freeze-drying to obtain copper porphyrin nanosheets; the volume ratio of N,N-dimethylformamide to ethanol in the mixed solution of N,N-dimethylformamide and ethanol is 3:1, and the ratio of the mass of the tetrakis(4-carboxyphenyl)porphine to the volume of the mixed solution of N,N-dimethylformamide and ethanol is 4.5:1, wherein the unit of mass is mg and the unit of volume is mL; the mass of the tetrakis(4-carboxyphenyl)porphine is 200% of the mass of cupric chloride dihydrate, and the mass of polyvinyl pyrrolidone is 120% of the mass of cupric chloride dihydrate;
[0069] Step 104, ultrasonically uniformly dispersing the MXene nanosheets described in step 102 and the copper porphyrin nanosheets described in step 103 in a mixed solution of N,N-dimethylformamide and ethanol to obtain a suspension containing copper porphyrin and MXene, heating in a water bath at 80°C, vigorously stirring for 6 hours, centrifuging and collecting at a speed of 5000 rpm, and freeze-drying to obtain MXene@CuTCPP nanosheets; the volume ratio of N,N-dimethylformamide to ethanol in the mixed solution of N,N-dimethylformamide and ethanol is 3:1, the mass of the MXene nanosheets is 125% of the mass of the copper porphyrin nanosheets, and the ratio of the mass of the MXene nanosheets to the volume of the mixed solution of N,N-dimethylformamide and ethanol is 4.5:1, wherein the unit of mass is mg and the unit of volume is mL;
[0070] Step 2: using EDC and NHS to modify the recombinant collagen to obtain modified recombinant collagen; the specific modification method includes:
[0071] Step 201, dissolving recombinant collagen, EDC and NHS in a phosphate buffer solution to obtain a mixed solution, stirring and activating the mixed solution at 37° C. for 1 hour to obtain an activated recombinant collagen solution; the pH of the mixed solution is 3.5; the mass of the recombinant collagen is 4% of the mass of the phosphate buffer solution; the molar ratio of EDC to NHS is 1:1;
[0072] Step 202, mixing the recombinant collagen solution activated in step 201 and the buffer solution containing 3-aminophenylboronic acid, stirring and reacting at 37° C. for 12 hours, dialyzing the system after stirring and reacting, and freeze-drying to obtain modified recombinant collagen; the amount of recombinant collagen substance is twice the amount of 3-aminophenylboronic acid substance; the buffer solution containing 3-aminophenylboronic acid is a buffer solution prepared by dissolving 3-aminophenylboronic acid in phosphate buffer, and the mass percentage of 3-aminophenylboronic acid in the buffer solution is 4%; the amount ratio of 3-aminophenylboronic acid, EDC and NHS is 1:1:1;
[0073] Step 3, sterilizing the MXene@CuTCPP composite nanoparticles prepared in step 1 by Co60 irradiation;
[0074] Step 4, dissolving the modified recombinant collagen described in step 2 in a phosphate buffer solution to obtain a modified recombinant collagen solution with a mass concentration of 10%;
[0075] Step 5: Mix the sterilized MXene@CuTCPP composite nanoparticles in step 3 with the modified recombinant collagen solution in step 4, and stir for 1 minute to obtain system A; the mass percentage of MXene@CuTCPP composite nanoparticles in system A is 0.3%;
[0076] Step six, add polyvinyl alcohol to deionized water, stir at 80°C for 20 minutes to obtain a polyvinyl alcohol solution with a mass fraction of 10%; the molecular weight of the polyvinyl alcohol is 89000; add the system A described in step five to the polyvinyl alcohol solution, stir and mix for 1 minute to obtain a recombinant collagen nanocomposite hydrogel for repairing wounds infected by multidrug-resistant bacteria; the mass ratio of the polyvinyl alcohol solution to the system A is 1:1.
[0077] Example 2
[0078] The method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multi-drug resistant bacteria of this embodiment comprises the following steps:
[0079] Step 1: Prepare MXene@CuTCPP composite nanoparticles using MXene nanosheets and copper porphyrin nanosheets; the specific preparation method includes:
[0080] Step 101, etching titanium aluminum carbide with hydrofluoric acid for 12 hours, centrifuging, and drying to obtain MXene multilayer nanosheets; the mass of the hydrofluoric acid is 5 times the mass of the titanium aluminum carbide, and the mass percentage of the hydrofluoric acid is 35%;
[0081] Step 102, exfoliating the MXene multilayer nanosheets in step 101 with a tetramethylammonium hydroxide solution for 24 hours, centrifuging, and drying to obtain a few-layer MXene nanosheet; the mass of the tetramethylammonium hydroxide solution is 7 times the mass of titanium aluminum carbide, and the mass percentage of tetramethylammonium hydroxide in the tetramethylammonium hydroxide solution is 40%;
[0082] Step 103, uniformly dispersing tetrakis(4-carboxyphenyl)porphine in a mixed solution of N,N-dimethylformamide and ethanol by ultrasonication to obtain a tetrakis(4-carboxyphenyl)porphine suspension, adding cupric chloride dihydrate and polyvinyl pyrrolidone to the suspension, heating in a water bath at 80° C., vigorously stirring for 5 h, collecting by centrifugation at a speed of 8000 rpm, and freeze-drying to obtain copper porphyrin nanosheets; the volume ratio of N,N-dimethylformamide to ethanol in the mixed solution of N,N-dimethylformamide and ethanol is 4:1, the ratio of the mass of the tetrakis(4-carboxyphenyl)porphine to the volume of the mixed solution of N,N-dimethylformamide and ethanol is 5:1, wherein the unit of mass is mg, and the unit of volume is mL; the mass of the tetrakis(4-carboxyphenyl)porphine is 150% of the mass of cupric chloride dihydrate, and the mass of the polyvinyl pyrrolidone is 100% of the mass of cupric chloride dihydrate;
[0083] Step 104, ultrasonically uniformly dispersing the MXene nanosheets described in step 102 and the copper porphyrin nanosheets described in step 103 in a mixed solution of N,N-dimethylformamide and ethanol to obtain a suspension containing copper porphyrin and MXene, heating in a water bath at 80°C, vigorously stirring for 7 hours, centrifuging and collecting at a speed of 5000 rpm, and freeze-drying to obtain MXene@CuTCPP nanosheets; the volume ratio of N,N-dimethylformamide to ethanol in the mixed solution of N,N-dimethylformamide and ethanol is 4:1, and the mass of the MXene nanosheet is 150% of the mass of the copper porphyrin nanosheet; the ratio of the mass of the MXene nanosheet to the volume of the mixed solution of N,N-dimethylformamide and ethanol is 5:1, wherein the unit of mass is mg and the unit of volume is mL;
[0084] Step 2: using EDC and NHS to modify the recombinant collagen to obtain modified recombinant collagen; the specific modification method includes:
[0085] Step 201, dissolving recombinant collagen, EDC and NHS in a phosphate buffer solution to obtain a mixed solution, stirring and activating the mixed solution at 36° C. for 1 hour to obtain an activated recombinant collagen solution; the pH of the mixed solution is 3.55; the mass of the recombinant collagen is 5% of the mass of the phosphate buffer solution; the molar ratio of EDC to NHS is 1:1;
[0086] Step 202, mixing the recombinant collagen solution activated in step 201 and the buffer solution containing 3-aminophenylboronic acid, stirring and reacting at 36° C. for 13 hours, dialyzing the system after stirring and reacting, and freeze-drying to obtain modified recombinant collagen; the amount of recombinant collagen substance is twice the amount of 3-aminophenylboronic acid substance; the buffer solution containing 3-aminophenylboronic acid is a buffer solution prepared by dissolving 3-aminophenylboronic acid in phosphate buffer, and the mass percentage of 3-aminophenylboronic acid in the buffer solution is 4%; the amount ratio of 3-aminophenylboronic acid, EDC and NHS is 1.5:1:1;
[0087] Step 3, sterilizing the MXene@CuTCPP composite nanoparticles prepared in step 1 by Co60 irradiation;
[0088] Step 4, dissolving the modified recombinant collagen described in step 2 in a phosphate buffer solution to obtain a modified recombinant collagen solution with a mass concentration of 12.5%;
[0089] Step 5: Mix the sterilized MXene@CuTCPP composite nanoparticles in step 3 with the modified recombinant collagen solution in step 4, and stir for 1 minute to obtain system A; the mass percentage of MXene@CuTCPP composite nanoparticles in system A is 0.2%;
[0090] Step six, add polyvinyl alcohol to deionized water, stir at 85°C for 20 minutes to obtain a polyvinyl alcohol solution with a mass fraction of 10%; the molecular weight of the polyvinyl alcohol is 89000; add the system A described in step five to the polyvinyl alcohol solution, stir and mix for 1 minute to obtain a recombinant collagen nanocomposite hydrogel for repairing wounds infected by multidrug-resistant bacteria; the mass ratio of the polyvinyl alcohol solution to the system A is 1:1.
[0091] Example 3
[0092] The method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multi-drug resistant bacteria of this embodiment comprises the following steps:
[0093] Step 1: Prepare MXene@CuTCPP composite nanoparticles using MXene nanosheets and copper porphyrin nanosheets; the specific preparation method includes:
[0094] Step 101, etching titanium aluminum carbide with hydrofluoric acid for 36 hours, centrifuging, and drying to obtain MXene multilayer nanosheets; the mass of the hydrofluoric acid is 5 times the mass of the titanium aluminum carbide, and the mass percentage of the hydrofluoric acid is 40%;
[0095] Step 102, exfoliating the MXene multilayer nanosheets in step 101 with a tetramethylammonium hydroxide solution for 18 hours, centrifuging, and drying to obtain a few-layer MXene nanosheet; the mass of the tetramethylammonium hydroxide solution is 10 times the mass of titanium aluminum carbide, and the mass percentage of tetramethylammonium hydroxide in the tetramethylammonium hydroxide solution is 30%;
[0096] Step 103, uniformly dispersing tetrakis(4-carboxyphenyl)porphine in a mixed solution of N,N-dimethylformamide and ethanol by ultrasonication to obtain a tetrakis(4-carboxyphenyl)porphine suspension, adding cupric chloride dihydrate and polyvinyl pyrrolidone to the suspension, heating in a water bath at 80° C., vigorously stirring for 6 h, collecting by centrifugation at a speed of 8000 rpm, and freeze-drying to obtain copper porphyrin nanosheets; the volume ratio of N,N-dimethylformamide to ethanol in the mixed solution of N,N-dimethylformamide and ethanol is 4:1, the ratio of the mass of the tetrakis(4-carboxyphenyl)porphine to the volume of the mixed solution of N,N-dimethylformamide and ethanol is 4:1, wherein the unit of mass is mg, and the unit of volume is mL; the mass of the tetrakis(4-carboxyphenyl)porphine is 175% of the mass of cupric chloride dihydrate, and the mass of polyvinyl pyrrolidone is 130% of the mass of cupric chloride dihydrate;
[0097] Step 104, ultrasonically uniformly dispersing the MXene nanosheets described in step 102 and the copper porphyrin nanosheets described in step 103 in a mixed solution of N,N-dimethylformamide and ethanol to obtain a suspension containing copper porphyrin and MXene, heating in a water bath at 80°C, vigorously stirring for 6.5h, centrifuging and collecting at a speed of 5000rpm, and freeze-drying to obtain MXene@CuTCPP nanosheets; the volume ratio of N,N-dimethylformamide to ethanol in the mixed solution of N,N-dimethylformamide and ethanol is 4:1, and the mass of the MXene nanosheets is 100% of the mass of the copper porphyrin nanosheets; the ratio of the mass of the MXene nanosheets to the volume of the mixed solution of N,N-dimethylformamide and ethanol is 4:1, wherein the unit of mass is mg and the unit of volume is mL;
[0098] Step 2: using EDC and NHS to modify the recombinant collagen to obtain modified recombinant collagen; the specific modification method includes:
[0099] Step 201, dissolving recombinant collagen, EDC and NHS in a phosphate buffer solution to obtain a mixed solution, stirring and activating the mixed solution at 36° C. for 1.5 h to obtain an activated recombinant collagen solution; the pH of the mixed solution is 3.56; the mass of the recombinant collagen is 5% of the mass of the phosphate buffer solution; the molar ratio of EDC to NHS is 1:1;
[0100] Step 202, mixing the recombinant collagen solution activated in step 201 and the buffer solution containing 3-aminophenylboronic acid, stirring and reacting at 36.5°C for 14 hours, dialyzing the system after stirring and reacting, and freeze-drying to obtain modified recombinant collagen; the amount of recombinant collagen substance is twice the amount of 3-aminophenylboronic acid substance; the buffer solution containing 3-aminophenylboronic acid is a buffer solution prepared by dissolving 3-aminophenylboronic acid in phosphate buffer, and the mass percentage of 3-aminophenylboronic acid in the buffer solution is 5%; the amount ratio of 3-aminophenylboronic acid, EDC and NHS is 1.2:1:1;
[0101] Step 3, sterilizing the MXene@CuTCPP composite nanoparticles prepared in step 1 by Co60 irradiation;
[0102] Step 4, dissolving the modified recombinant collagen described in step 2 in a phosphate buffer solution to obtain a modified recombinant collagen solution with a mass concentration of 10%;
[0103] Step 5, mixing the sterilized MXene@CuTCPP composite nanoparticles in step 3 with the modified recombinant collagen solution in step 4, and stirring for 2 minutes to obtain system A; the mass percentage of MXene@CuTCPP composite nanoparticles in system A is 0.5%;
[0104] Step six, add polyvinyl alcohol to deionized water, stir at 85°C for 20 minutes, and obtain a polyvinyl alcohol solution with a mass fraction of 15%; the molecular weight of the polyvinyl alcohol is 89000; add the system A described in step five to the polyvinyl alcohol solution, stir and mix for 2 minutes, and obtain a recombinant collagen nanocomposite hydrogel for repairing wounds infected by multidrug-resistant bacteria; the mass ratio of the polyvinyl alcohol solution to the system A is 1:1.
[0105] Example 4
[0106] The method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multi-drug resistant bacteria of this embodiment comprises the following steps:
[0107] Step 1: Prepare MXene@CuTCPP composite nanoparticles using MXene nanosheets and copper porphyrin nanosheets; the specific preparation method includes:
[0108] Step 101, etching titanium aluminum carbide with hydrofluoric acid for 24 hours, centrifuging, and drying to obtain MXene multilayer nanosheets; the mass of the hydrofluoric acid is 7.5 times the mass of the titanium aluminum carbide, and the mass percentage of the hydrofluoric acid is 45%;
[0109] Step 102, exfoliating the MXene multilayer nanosheets in step 101 with a tetramethylammonium hydroxide solution for 24 hours, centrifuging, and drying to obtain a few-layer MXene nanosheet; the mass of the tetramethylammonium hydroxide solution is 5 times the mass of titanium aluminum carbide, and the mass percentage of tetramethylammonium hydroxide in the tetramethylammonium hydroxide solution is 30%;
[0110] Step 103, ultrasonically uniformly dispersing tetrakis(4-carboxyphenyl)porphine in a mixed solution of N,N-dimethylformamide and ethanol to obtain a tetrakis(4-carboxyphenyl)porphine suspension, adding cupric chloride dihydrate and polyvinyl pyrrolidone to the suspension, heating in a water bath at 70° C., vigorously stirring for 9 hours, centrifuging and collecting at a speed of 8000 rpm, and then freeze-drying to obtain copper porphyrin nanosheets; the volume ratio of N,N-dimethylformamide to ethanol in the mixed solution of N,N-dimethylformamide and ethanol is 4:1, and the ratio of the mass of the tetrakis(4-carboxyphenyl)porphine to the volume of the mixed solution of N,N-dimethylformamide and ethanol is 4:1, wherein the unit of mass is mg, and the unit of volume is mL; the mass of the tetrakis(4-carboxyphenyl)porphine is 175% of the mass of cupric chloride dihydrate, and the mass of polyvinyl pyrrolidone is 130% of the mass of cupric chloride dihydrate;
[0111] Step 104, ultrasonically uniformly dispersing the MXene nanosheets described in step 102 and the copper porphyrin nanosheets described in step 103 in a mixed solution of N,N-dimethylformamide and ethanol to obtain a suspension containing copper porphyrin and MXene, heating in a water bath at 70°C, vigorously stirring for 9 hours, centrifuging and collecting at a speed of 5000 rpm, and freeze-drying to obtain MXene@CuTCPP nanosheets; the volume ratio of N,N-dimethylformamide to ethanol in the mixed solution of N,N-dimethylformamide and ethanol is 4:1, and the mass of the MXene nanosheet is 150% of the mass of the copper porphyrin nanosheet; the ratio of the mass of the MXene nanosheet to the volume of the mixed solution of N,N-dimethylformamide and ethanol is 4:1, wherein the unit of mass is mg and the unit of volume is mL;
[0112] Step 2: using EDC and NHS to modify the recombinant collagen to obtain modified recombinant collagen; the specific modification method includes:
[0113] Step 201, dissolving recombinant collagen, EDC and NHS in a phosphate buffer solution to obtain a mixed solution, stirring and activating the mixed solution at 37° C. for 1.5 h to obtain an activated recombinant collagen solution; the pH of the mixed solution is 4; the mass of the recombinant collagen is 4% of the mass of the phosphate buffer solution; the molar ratio of EDC to NHS is 1:1;
[0114] Step 202, mixing the recombinant collagen solution activated in step 201 and the buffer solution containing 3-aminophenylboronic acid, stirring and reacting at 37° C. for 14 hours, dialyzing the system after stirring and reacting, and freeze-drying to obtain modified recombinant collagen; the amount of recombinant collagen substance is 1.5 times the amount of 3-aminophenylboronic acid substance; the buffer solution containing 3-aminophenylboronic acid is a buffer solution prepared by dissolving 3-aminophenylboronic acid in phosphate buffer, and the mass percentage of 3-aminophenylboronic acid in the buffer solution is 5%; the amount ratio of 3-aminophenylboronic acid, EDC and NHS is 1:1:1;
[0115] Step 3, sterilizing the MXene@CuTCPP composite nanoparticles prepared in step 1 by Co60 irradiation;
[0116] Step 4, dissolving the modified recombinant collagen described in step 2 in a phosphate buffer solution to obtain a modified recombinant collagen solution with a mass concentration of 12.5%;
[0117] Step 5, mixing the sterilized MXene@CuTCPP composite nanoparticles in step 3 with the modified recombinant collagen solution in step 4, and stirring for 2 minutes to obtain system A; the mass percentage of MXene@CuTCPP composite nanoparticles in system A is 0.4%;
[0118] Step six, add polyvinyl alcohol to deionized water, stir at 90°C for 20 minutes to obtain a polyvinyl alcohol solution with a mass fraction of 10%; the molecular weight of the polyvinyl alcohol is 98000; add the system A described in step five to the polyvinyl alcohol solution, stir and mix for 2 minutes to obtain a recombinant collagen nanocomposite hydrogel for repairing wounds infected by multidrug-resistant bacteria; the mass ratio of the polyvinyl alcohol solution to the system A is 1:2.
[0119] Example 5
[0120] The method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multi-drug resistant bacteria of this embodiment comprises the following steps:
[0121] Step 1: Prepare MXene@CuTCPP composite nanoparticles using MXene nanosheets and copper porphyrin nanosheets; the specific preparation method includes:
[0122] Step 101, etching titanium aluminum carbide with hydrofluoric acid for 96 hours, centrifuging, and drying to obtain MXene multilayer nanosheets; the mass of the hydrofluoric acid is 10 times the mass of the titanium aluminum carbide, and the mass percentage of the hydrofluoric acid is 30%;
[0123] Step 102, exfoliating the MXene multilayer nanosheets in step 101 with a tetramethylammonium hydroxide solution for 48 hours, centrifuging, and drying to obtain a few-layer MXene nanosheet; the mass of the tetramethylammonium hydroxide solution is 5 times the mass of titanium aluminum carbide, and the mass percentage of tetramethylammonium hydroxide in the tetramethylammonium hydroxide solution is 50%;
[0124] Step 103, uniformly dispersing tetrakis(4-carboxyphenyl)porphine in a mixed solution of N,N-dimethylformamide and ethanol by ultrasonication to obtain a tetrakis(4-carboxyphenyl)porphine suspension, adding cupric chloride dihydrate and polyvinyl pyrrolidone to the suspension, heating in a water bath at 90° C., vigorously stirring for 5 h, collecting by centrifugation at a speed of 8000 rpm, and freeze-drying to obtain copper porphyrin nanosheets; the volume ratio of N,N-dimethylformamide to ethanol in the mixed solution of N,N-dimethylformamide and ethanol is 3.5:1, the ratio of the mass of the tetrakis(4-carboxyphenyl)porphine to the volume of the mixed solution of N,N-dimethylformamide and ethanol is 4:1, wherein the unit of mass is mg, and the unit of volume is mL; the mass of the tetrakis(4-carboxyphenyl)porphine is 200% of the mass of cupric chloride dihydrate, and the mass of polyvinyl pyrrolidone is 100% of the mass of cupric chloride dihydrate;
[0125] Step 104, ultrasonically uniformly dispersing the MXene nanosheets described in step 102 and the copper porphyrin nanosheets described in step 103 in a mixed solution of N,N-dimethylformamide and ethanol to obtain a suspension containing copper porphyrin and MXene, heating in a water bath at 90°C, vigorously stirring for 5h, centrifuging and collecting at a speed of 5000rpm, and freeze-drying to obtain MXene@CuTCPP nanosheets; the volume ratio of N,N-dimethylformamide to ethanol in the mixed solution of N,N-dimethylformamide and ethanol is 3.5:1, and the mass of the MXene nanosheet is 80% of the mass of the copper porphyrin nanosheet; the ratio of the mass of the MXene nanosheet to the volume of the mixed solution of N,N-dimethylformamide and ethanol is 5:1, wherein the unit of mass is mg and the unit of volume is mL;
[0126] Step 2: using EDC and NHS to modify the recombinant collagen to obtain modified recombinant collagen; the specific modification method includes:
[0127] Step 201, dissolving recombinant collagen, EDC and NHS in a phosphate buffer solution to obtain a mixed solution, stirring and activating the mixed solution at 20° C. for 3 hours to obtain an activated recombinant collagen solution; the pH of the mixed solution is 3; the mass of the recombinant collagen is 4.5% of the mass of the phosphate buffer solution; the molar ratio of EDC to NHS is 1:1;
[0128] Step 202, mixing the recombinant collagen solution activated in step 201 and the buffer solution containing 3-aminophenylboronic acid, stirring and reacting at a temperature of 20° C. for 16 hours, dialyzing the system after the stirring reaction, and freeze-drying to obtain modified recombinant collagen; the amount of the recombinant collagen substance is 1.8 times the amount of the 3-aminophenylboronic acid substance; the buffer solution containing 3-aminophenylboronic acid is a buffer solution prepared by dissolving 3-aminophenylboronic acid in phosphate buffer, and the mass percentage of 3-aminophenylboronic acid in the buffer solution is 4.5%; the amount ratio of 3-aminophenylboronic acid, EDC and NHS is 1.5:1:1;
[0129] Step 3, sterilizing the MXene@CuTCPP composite nanoparticles prepared in step 1 by Co60 irradiation;
[0130] Step 4, dissolving the modified recombinant collagen described in step 2 in a phosphate buffer solution to obtain a modified recombinant collagen solution with a mass concentration of 15%;
[0131] Step 5: Mix the sterilized MXene@CuTCPP composite nanoparticles in step 3 with the modified recombinant collagen solution in step 4, and stir for 1 minute to obtain system A; the mass percentage of MXene@CuTCPP composite nanoparticles in system A is 0.5%;
[0132] Step six, add polyvinyl alcohol to deionized water, stir at 80°C for 20 minutes, and obtain a polyvinyl alcohol solution with a mass fraction of 12.5%; the molecular weight of the polyvinyl alcohol is 95000; add the system A described in step five to the polyvinyl alcohol solution, stir and mix for 2 minutes, and obtain a recombinant collagen nanocomposite hydrogel for repairing wounds infected by multidrug-resistant bacteria; the mass ratio of the polyvinyl alcohol solution to the system A is 2:1.
[0133] Performance Evaluation
[0134] The MXene@CuTCPP composite nanoparticles prepared by the present invention were ultrasonically dispersed uniformly in deionized water, diluted to a certain concentration, and dropped on the surface of a silicon wafer. The sample was allowed to stand for drying, and then placed on a conductive adhesive for gold spraying. The sample morphology was observed by scanning electron microscopy. Figure 2 ,It can be seen from the figure that the surface of MXene is covered with an ultra-thin layer of nanosheets. At the same time, the mapping element distribution map of MXene@CuTCPP shows the unique Cu element distribution of CuTCPP, which proves the successful modification of MXene.
[0135] The dried MXene@CuTCPP composite nanoparticle powder sample prepared by the present invention was placed in the groove of the slide, and the surface was flattened with a cover glass. The parameters were set to 5° / min and the angle range was 5-90° for X-ray powder diffraction test. The results are shown in Figure 3 ,It can be seen from the figure that the main diffraction peaks of MXene@CuTCPP are derived from MXene and CuTCPP, and no new diffraction peaks are formed.
[0136] The modified recombinant collagen powder sample prepared in Example 1 of the present invention was placed on a tablet press to prepare the sample, and the FT-IR spectrum of the sample was recorded using an infrared spectrometer. The test wave number range was 500 cm -1 Up to 4000cm -1 The results are shown in Figure 4 CF-1552 is recombinant collagen, and APBA-CF-1552 is modified recombinant collagen; in the spectrum of CF-1552, 1727cm -1 The infrared spectrum of APBA-CF-1552 shows the absorption peaks of m-substituted benzene and carbonyl groups. -1 The stretching vibration peak of amide appeared at ; compared with the ungrafted CF-1552, the absorption of its carbonyl group was weakened. This is because the lone pair of electrons in the nitrogen element of the amide group formed a conjugated system with the carbonyl group, producing an inductive effect, thereby reducing the absorption of its carbonyl group. From this, it can be preliminarily judged that APBA-CF-1552 was successfully prepared.
[0137] Figure 5 This is a morphology diagram of the recombinant collagen nanocomposite hydrogel used for repairing wounds infected with multi-drug resistant bacteria in Example 1 of the present invention. It can be seen from the figure that the morphology of the recombinant collagen nanocomposite hydrogel is moist and soft. The recombinant collagen nanocomposite hydrogel prepared in Example 1 of the present invention was quickly frozen in liquid nitrogen for 20 minutes, and then placed in a freeze dryer for freeze drying for 3 to 4 days. The sample was taken out for brittle fracture and gold spraying, and the sample morphology was observed by scanning electron microscopy. The results are shown in Figure 6 ,As can be seen from the figure, the internal structure of the ,recombinant collagen nanocomposite hydrogel presents uniform pores, which can absorb the ,internal fluid exuded from the wound.
[0138] RPMI-1640 medium was used to culture 1.0 × 10 4L929 cells were inoculated in a 96-well plate at an initial density of 10 cells, and incubated in a cell culture incubator for 24 hours. The hydrogel of the present invention was immersed in RPMI-1640 culture medium at a concentration of 0.1 g / mL, and extracted for 2 to 3 days to obtain a hydrogel extract. The original culture medium was replaced with the hydrogel extract, and the culture was incubated in a cell culture incubator for 24 to 48 hours. The cytotoxicity was tested by CCK-8 colorimetry. The results are shown in FIG. Figure 7 The results showed that the cytotoxicity of the hydrogel was maintained above 97%. The scratch method was used to investigate the migration behavior of the cells. RPMI-1640 medium was used at 1.0×10 4 L929 cells were inoculated in a 96-well plate at an initial density of 10 cells, incubated in a cell culture incubator for 24 h, then the cell layer was scratched with a pipette tip, the original culture medium was replaced with the above hydrogel extract, incubated in a cell culture incubator for 12 h, and the cell growth was observed under a microscope. Figure 8 The results showed that the hydrogel has the effect of promoting wound healing. Figure 7 and 8 All of these results show that the hydrogel has excellent biocompatibility.
[0139] MXene@CuTCPP samples with different concentrations were placed in 1 mL MRSA suspension (10 5 CFU / mL) and co-cultured for 12 h in a 37°C shaker (100 rpm). The addition of H2O2 in another group was to simulate the state in which H2O2 would be produced in the wound after wound infection. The control group contained only 1 mL of bacterial suspension and then co-cultured. After the culture was completed, the bacterial suspension was diluted to 10 3 CFU / mL, fully resuspend and take 100μL to drop on solid culture medium, evenly spread with a coating rod, and incubate in a 37℃ incubator for 12h. Observe the number of colonies and calculate the bacterial survival rate. The in vitro antibacterial experiments of the other two bacteria are the same as above. The results are shown in Fig. 9 , Fig.10 and Fig.11 As can be seen from the figure, the composite nanoparticles have obvious antibacterial properties against the three bacteria. At a concentration of 1g / mL MXene@CuTCPP, the bacterial survival rates of MRSA, S.aureus and E.coli do not exceed 10%. MXene@CuTCPP itself is negatively charged and will adsorb more MRSA (Gram-positive coagulase-positive pathogens) and Gram-positive bacteria (S.aureus), resulting in better antibacterial properties than E.coli.
[0140] Figure 12-14The results are as follows: The in vitro antibacterial experiments and bacterial survival rates of S. aureus, E. coli and MRSA under near-infrared irradiation and different treatment methods of hydrogels. The hydrogel designed by the present invention treats multi-drug resistant bacterial wounds by using both PTT and PDT. PTT mainly converts light energy into heat, increases the local temperature of the wound and kills bacteria by thermal damage. The MXene@CuTCPP heterojunction structure can effectively kill bacteria by catalyzing H2O2 to generate ROS. Samples of different hydrogels were placed in MRSA suspension (10 5 CFU / mL) and co-cultured for 12 h in a 37°C shaker (100 rpm). In the other group, H2O2 was added to simulate the state in which H2O2 would be produced in the wound after wound infection. After co-culture, the bacterial solution was diluted to 10 3 CFU / mL, fully resuspend and take 100μL to drop on the solid culture medium, evenly spread with a coating rod, and incubate in a 37℃ incubator for 12h. The bacterial survival rate was calculated by observing the number of colonies, and the in vitro antibacterial experiments of the other two bacteria were the same as above. By comparison, it can be concluded that the addition of MXene@CuTCPP greatly improves the photothermal performance of the hydrogel, and the antibacterial effects of the CAP / MXene@CuTCPP+NIR group and the CAP / MXene@CuTCPP+H2O2+NIR group are more obvious. In particular, the antibacterial effect of the full material group is the best.
[0141] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a recombinant collagen nanocomposite hydrogel for repairing wounds infected with multidrug-resistant bacteria, characterized in that: The following steps are involved: Step 1: Prepare MXene@CuTCPP composite nanoparticles using MXene nanosheets and copper porphyrin nanosheets; Step 2: using EDC and NHS to modify the recombinant collagen to obtain modified recombinant collagen; Step 3, sterilizing the MXene@CuTCPP composite nanoparticles prepared in step 1 by Co60 irradiation; Step 4, dissolving the modified recombinant collagen described in step 2 in a phosphate buffer solution to obtain a modified recombinant collagen solution with a mass concentration of 10% to 15%; Step 5: Mix the sterilized MXene@CuTCPP composite nanoparticles in step 3 with the modified recombinant collagen solution in step 4, and stir for 1 min to 2 min to obtain system A; Step 6: Add the system A described in step 5 into the polyvinyl alcohol solution and mix them evenly to obtain a recombinant collagen nanocomposite hydrogel for repairing wounds infected with multidrug-resistant bacteria.
2. The method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multi-drug resistant bacteria according to claim 1, characterized in that: The preparation method of MXene@CuTCPP composite nanoparticles in step 1 specifically includes: Step 101, etching titanium aluminum carbide with hydrofluoric acid for 12 hours to 96 hours, centrifuging, and drying to obtain MXene multilayer nanosheets; Step 102, exfoliating the MXene multilayer nanosheets described in step 101 with a tetramethylammonium hydroxide solution for 12 h to 48 h, centrifuging, and drying to obtain a few-layer MXene nanosheet; Step 103, uniformly dispersing tetrakis(4-carboxyphenyl)porphine in a mixed solution of N,N-dimethylformamide and ethanol by ultrasonication to obtain a tetrakis(4-carboxyphenyl)porphine suspension, adding cupric chloride dihydrate and polyvinyl pyrrolidone to the suspension, heating in a water bath at 70° C. to 90° C., vigorously stirring for 5 h to 9 h, centrifuging and freeze-drying to obtain copper porphyrin nanosheets; Step 104: Ultrasonically uniformly disperse the MXene nanosheets described in step 102 and the copper porphyrin nanosheets described in step 103 in a mixed solution of N,N-dimethylformamide and ethanol to obtain a suspension containing copper porphyrin and MXene, heat in a water bath at 70° C. to 90° C., vigorously stir for 5 h to 9 h, centrifuge, and freeze-dry to obtain MXene@CuTCPP nanosheets.
3. The method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multi-drug resistant bacteria according to claim 2, characterized in that: The mass of the hydrofluoric acid described in step 101 is 5 to 10 times the mass of titanium aluminum carbide, and the mass percentage of the hydrofluoric acid is 30% to 45%; the mass of the tetramethylammonium hydroxide solution described in step 102 is 5 to 10 times the mass of titanium aluminum carbide, and the mass percentage of tetramethylammonium hydroxide in the tetramethylammonium hydroxide solution is 25% to 50%.
4. The method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multi-drug resistant bacteria according to claim 2, characterized in that: In step 103, the volume ratio of N,N-dimethylformamide to ethanol in the mixed solution of N,N-dimethylformamide and ethanol is (3-4):1; the ratio of the mass of the tetrakis(4-carboxyphenyl)porphine to the volume of the mixed solution of N,N-dimethylformamide and ethanol is (4-5):1, wherein the unit of mass is mg and the unit of volume is mL; the mass of the tetrakis(4-carboxyphenyl)porphine is 150%-200% of the mass of cupric chloride dihydrate, and the mass of polyvinyl pyrrolidone is The mass of the mixed solution of N,N-dimethylformamide and ethanol in step 104 is 100% to 130% of the mass of cupric chloride dihydrate; the volume ratio of N,N-dimethylformamide to ethanol in the mixed solution of N,N-dimethylformamide and ethanol is (3 to 4):1, the mass of the MXene nanosheets is 80% to 150% of the mass of the copper porphyrin nanosheets, and the ratio of the mass of the MXene nanosheets to the volume of the mixed solution of N,N-dimethylformamide and ethanol is (4 to 5):1, wherein the unit of mass is mg and the unit of volume is mL.
5. The method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multi-drug resistant bacteria according to claim 1, characterized in that: The modification method in step 2 specifically includes: Step 201, dissolving recombinant collagen, EDC and NHS in a phosphate buffer solution to obtain a mixed solution, stirring and activating the mixed solution at a temperature of 20° C. to 37° C. for 1 h to 3 h to obtain an activated recombinant collagen solution; Step 202, mixing the recombinant collagen solution activated in step 201 and the buffer solution containing 3-aminophenylboronic acid, stirring and reacting at a temperature of 20°C to 37°C for 12h to 16h, dialyzing the system after the stirring reaction, and freeze-drying to obtain modified recombinant collagen.
6. The method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected by multi-drug resistant bacteria according to claim 5, characterized in that: The pH of the mixed solution in step 201 is 3-4; the mass of the recombinant collagen is 4%-5% of the mass of the phosphate buffer solution.
7. The method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multi-drug resistant bacteria according to claim 5, characterized in that: The recombinant collagen described in step 201 is recombinant collagen CF-1552, and the amount of the recombinant collagen substance is 1.5 to 2 times the amount of the 3-aminophenylboronic acid substance in step 202; the buffer solution containing 3-aminophenylboronic acid in step 202 is a buffer solution prepared by dissolving 3-aminophenylboronic acid in phosphate buffer, and the mass percentage of 3-aminophenylboronic acid in the buffer solution is 4% to 5%; the molar ratio of 3-aminophenylboronic acid, EDC and NHS is (1 to 1.5):1:
1.
8. The method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multi-drug resistant bacteria according to claim 1, characterized in that: The mass percentage of MXene@CuTCPP composite nanoparticles in the system A of step 5 is 0.2% to 0.5%.
9. The method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected with multi-drug resistant bacteria according to claim 1, characterized in that: The polyvinyl alcohol solution in step six is a polyvinyl alcohol aqueous solution with a mass concentration of 10% to 15%, and the molecular weight of the polyvinyl alcohol is 89,000 to 98,000.
10. The method for preparing the recombinant collagen nanocomposite hydrogel for repairing wounds infected by multi-drug resistant bacteria according to claim 1, characterized in that: In step six, the mass ratio of the polyvinyl alcohol solution to the system A is (1-2):(1-2).
Citation Information
Patent Citations
Human like collagen and production method thereof
CN1371919A
Composite hydrogel for promoting wound healing as well as preparation method and application thereof
CN116251056A
Preparation method and application of near-infrared photothermal response composite antibacterial hydrogel adhesive
CN118718070A
Cited By
Acoustic power driven Janus hydrogel as well as preparation method and application thereof
CN121731202A
Microneedle patch for closed-loop management of drug-resistant bacteria infected wounds of animals as well as preparation method and application of microneedle patch
CN121868039A